Factors Influencing the Adoption of Mobile Payment Method among Generation Z: the Extended UTAUT Approach - Triasesiarta nur; Rosinta Ria Panggabean (Journal of Accounting Research, Organization and Economics, 2021)
Objective– Rapid advances in financial technology have tremendously changed both the way of life and the way of doing business over recent decades. The ubiquitous usage of the internet is fostering new forms of enterprise. Mobile payment is a new way to conveniently and effectively conduct financial transactions through digital platforms. This study analyzes the factors influencing the adoption of mobile payments as a method of payment utilized by Generation Z. Generation Z represents the successor of the generation of our society and the generation that interacts the most with internet technology. Design/methodology– Using the Extended Unified Theory of Acceptance and Use of Technology (UTAUT) model, this study sampled 100 respondents of Generation Z from Jakarta and surrounding areas (JABODETABEK) and further analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM).  Results – The results show that factors relating to Performance Expectancy, Social Influences, Facilitating Condition, Perceived Enjoyment, and Trust significantly affect the Behavioral Intention to use mobile payments to conduct online transactions. Effort Expectancy shows no significant effect. Contribution – This study provided the evidence about the factors influencing the Generation Z’s intention behavior to adopt mobile payment technology as a tool in online purchasing, using the extended UTAUT model. This stems from extended UTAUT and applies it to explore how the Behavioral Intention of Generation Z in adopting mobile payment technology.